The Relevance of Muslim Identity Voters in Elections in Banjarnegara Regency - Munadi, Munadi (Unnes Political Science Journal, 2024)
General elections (elections) in Indonesia are often influenced by identity factors, especially religious identity. This article explains the relevance of Muslim identity voters in the context of elections. This study shows that religious identity plays a significant role in influencing the behavior of Muslim voters. Muslim voters tend to choose candidates who represent Islamic values and symbols, such as religious appearances and support for religious issues. This study uses experimental survey data that compares voters' responses to candidates with religious and secular appearances, this is closely related to genetic theory in human anthropology as a central actor in the electoral cosmos. The results showed that Muslim voters were more likely to support religious-looking candidates, such as religious-looking women and secular-looking men who supported religious issues. In addition, this article also discusses identity polarization that plays a role in encouraging voter participation. Identity polarization makes elections emotional and religious identity is one of the main factors in choosing candidates.